Development of Scıentıfıc-Based LKPD to Improve Students' Problem-Solvıng Abılıty - Lisnawati; Sutiarso, Sugeng; Hanurawati, Nur; Choirudin; Damayanti, Rani (Jurnal Pendidikan Matematika (JPM), 2023)
This study aims to determine the process and results of developing scientific-based mathematics learning worksheets that meet valid and practical criteria and test the developed worksheets' validity, practicality, and effectiveness. This research and development refer to the steps of Borg and Gall. The research subjects were grade VIII students of the Qur'an Science Middle School Minhajuth Thullab Pekalongan for the 2022/2023 academic year: data collection techniques using interviews, problem-solving ability tests, and questionnaires. The results showed that the LKPD teaching materials developed were categorized as valid (fit for use) based on the assessment of media and material expert validators. In addition, the developed scientific-based LKPD is also categorized as practical based on student assessments and responses from the mathematics teacher. Based on hypothesis testing and proportions, the scientific-based LKPD can improve problem-solving skills, but it is not yet effective because the proportion of students with good category problem-solving abilities is not more than 60% of the total number of students.